Character Value Management Through Leading Religion-Based School Programs in The City of Semarang - Nurhafizah, Nurhafizah; Budi Utomo, Cahyo; Made Sudana, I (Educational Management, 2021)
The purpose of this research was to describe the management of character values ​​through the flagship program of religious-based schools in the city of Semarang. This study used descriptive qualitative method. The data collection technique used is purposive sampling. The subjects of this study were the principals and teachers of SD QU Hanifah Semarang. Data collection techniques used in-depth interviews, observation, and documentation studies. The data validity technique uses source triangulation and theoretical triangulation. The results of this study indicate that the management of character values ​cultivation through the flagship program of religion-based schools in the city of Semarang is running well, it can be seen from the types of program activities that have been carried out not out of the school's vision, mission and goals. The types of activity programs that have been determined are the flagship program of Tahfidz and the flagship program of Parenting Day. In the program component, there is the role of principals and teachers as implementers of program development activities to instill character values ​​in students in everyday life. The implication of this research is to provide an overview of the role of principals, teachers, and parents of students at school and at home in instilling good character values ​​to students in the process of implementing the superior program that has been determined.